The Augmented R-Loop Is a Unifying Mechanism for Myelodysplastic Syndromes Induced by High-Risk Splicing Factor Mutations - Chen, Liang; Chen, Jia-Yu; Huang, Yi-Jou; Gu, Ying; Qiu, Jinsong; Qian, Hao; Shao, Changwei; Zhang, Xuan; Hu, Jing; Li, Hairi; He, Shunmin; Zhou, Yu; et al. (Molecular cell, 2018)
Mutations in several general pre-mRNA splicing factors have been linked to myelodysplastic syndromes (MDSs) and solid tumors. These mutations have generally been assumed to cause disease by the resultant splicing defects, but different mutations appear to induce distinct splicing defects, raising the possibility that an alternative common mechanism is involved. Here we report a chain of events triggered by multiple splicing factor mutations, especially high-risk alleles in SRSF2 and U2AF1, including elevated R-loops, replication stress, and activation of the ataxia telangiectasia and Rad3-related protein (ATR)-Chk1 pathway. We further demonstrate that enhanced R-loops, opposite to the expectation from gained RNA binding with mutant SRSF2, result from impaired transcription pause release because the mutant protein loses its ability to extract the RNA polymerase II (Pol II) C-terminal domain (CTD) kinase—the positive transcription elongation factor complex (P-TEFb)—from the 7SK complex. Enhanced R-loops are linked to compromised proliferation of bone-marrow-derived blood progenitors, which can be partially rescued by RNase H overexpression, suggesting a direct contribution of augmented R-loops to the MDS phenotype. [Display omitted] •Mutations in splicing factors cause cell cycle arrest but distinct splicing defects•Causal mutations in SRSF2 and U2AF1 activate the ATR, but not ATM, pathway•R-loops are augmented genome-wide in SRSF2 and U2AF1 mutants•Overexpressed RNase H partially corrects growth defect of hematopoietic progenitors Chen et al. report that myelodysplastic syndrome-associated mutations in splicing factors, including SRSF2 and U2AF1, cause cell growth defects through elevated R-loops, replication stress, and ATR-Chk1 activation. Mutant SRSF2 induces transcription pausing and, thus, R-loops, possibly because of its compromised ability in extracting p-TEFb from the 7SK complex at TSSs.